Challenges of Peer Tutoring in Different Role Organization Settings in Higher Education: Systematic Literature Review - Widoro, Ego; Situmorang, Robinson; Chaeruman, Uwes Anis (Pedagogika, 2024)
This systematic review aims to compare peer tutoring implementation with its role setting by identifying the challenges reported in previous studies. A total of 28 articles were systematically selected and reviewed. The challenges associated with the implementation of four peer tutoring settings, namely same-level and equal-status, same-level and unequal-status, cross-level and unequal-status, and cross-level and unequal-status settings in which the participants from different institutions, were examined.